TRANSFORMATION OF ISLAMIC AND CHARACTER EDUCATION LEARNING FOR THE URBAN MUSLIM GENERATION: A STUDY OF DIGITAL MODULE DEVELOPMENT IN ACEH - Wahyudi, Dedi; Idris, Jamaluddin; Jannah, Misbahul; Binti Borhan, Noziati; Silahuddin, Silahuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
Islamic and character education learning among urban Muslim students is facing serious challenges, such as low digital literacy, limited access to devices and the internet, as well as a scarcity of media suitable for the characteristics of digital generation. Therefore, this study aimed to develop a relevant and interactive flipbook-based digital module with Islamic character values to enhance the effectiveness of learning in the technological era. SMA Negeri 13 Banda Aceh was used because the Senior High School implemented Islamic law not found in other schools in Indonesia. The method applied was consistent with the Alessi and Trollip model, which included planning, design, and development. Additionally, this developmental study comprised learning module, in digital format, produced using Flip PDF Corporate Edition Version 2.4.10.3 in line with the Merdeka curriculum. Digital module was considered very feasible, with a percentage of 88.20% based on evaluations from material and media experts. According to the assessment of teachers and students, module was also very practical, with a rate of 91.59%. The results showed that development of digital-based Islamic and character education learning in Banda Aceh City secondary schools, in the form of digital module at SMA Negeri 13 Banda Aceh, was feasible and practical for use in learning. Digital module solved student learning problems in urban Muslim society by providing access to relevant, easy-to-use, and contextual materials to address the challenges of religious life in urban areas. Moreover, the results report the distinction of Islamic education by emphasizing the integration of values ​​in the context of modern life through an adaptive and contextual digital method.